Tales of a fourth grade nothing - Blume, Judy.; Doty, Roy, 1922- (New York : Bantam Doubleday Dell Books for Young Readers, 1991)
Peter finds his demanding two-year-old brother an ever-increasing problem.
"A Yearling book.".
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
4.9
3-6
Keywords: Brothers -- Fiction; Family life -- Fiction; Humorous stories; Sibling rivalry -- Fiction; Brothers -- Fiction; Family life -- Fiction; Humorous fiction; Sibling rivalry -- Fiction